PENGARUH MANAJEMEN LABA, KINERJA KEUANGAN DAN MILITARY CONNECTION TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi Empiris pada Perusahaan Mining yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2019) - Utpala, Clara Galuh; Adiwibowo, Agustinus Santosa (Diponegoro Journal of Accounting, 2021)
The purpose of this research is to examine the effect of earnings management, financial performance, and military connection to corporate social responsibility on mining companies. Variables used in the examination are earnings management, financial performance, and military connection as the independent variables, also corporate social responsibility as the dependent variable. This research used mining companies during the 2016-2019 with total sample is 128 samples. Sampling based on purposive sampling method that follows certain criteria(s). Multiple regression analysis is the analysis method used in this research. The results of this study indicates that earnings management and ROA have a positive significant effect on corporate social responsibility. ROE has a positive insignificant on corporate social responsibility. Beside that, military connection have a negative and insignificant on corporate social responsibility.